Chip distortion error post-processing method based on dynamic performance index of system response for multipath measurement. (July 2022) - Lu, Hui; Zhang, Ruoliu; Cao, Xianbin; Lei, Wanjun
Highlights: Based on system response, the reason for the distortion of rectangle waveform correlation function was analyzed. The dynamic response index of system was used to correct the multipath estimation error caused by system bandwidth limitation. Post-processing method could be combined with multipath estimation algorithms as the error compensation strategy. Wasserstein distance was used to measure multipath estimation results in simulation. The channel measurement system was designed to verify the proposed method in real environment. Abstract: Multipath effect is one crucial impact on the performance of wireless communication systems. Multipath measurement has attracted more attention. While in the multipath measurement system, the band-limited issue causes chip distortion and brings errors in results. This paper proposed a chip distortion error post-processing method for multipath estimation algorithm. First, the method uses the dynamic performance index of system response, to analyze the effect of overshoot on the distortion of the correlation function and deduce three parameters. Second, the method uses the three parameters to correct estimation errors. Finally, the proposed method is tested in simulated and practical environment. For simulated experiments, Wasserstein distance is adopted as the evaluation index. We construct the multipath measurement system for practical experiments to obtain the main paths and measurement error. The statistical results show that the proposed post-processing method is useful in alleviating estimation errors caused by band-limited issues.